BIAS BUDAYA DALAM TES PSIKOLOGI DITINJAU DARI ASPEK TESTEE DAN ALTERNATIF SOLUSINYA - WAHIDAH FITRIANI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
Various kinds of psychological tests have been administered in Indonesia. Unfortunately, almost all of them are adapted from different culture. This in turn will create new problems since those test are designed by developed countries. Since the tests contain different languages, attributes, norms and values, the biases are unavoidable. Cultural biases, for instance, are not only found in terms of content and methodology only, but also in caused by the tester and testee as as well.Kata kunci: bias budaya, tes psikologi, tester, testee